Embolization of unruptured wide-necked aneurysms at the MCA bifurcation using the Neuroform atlas stent-assisted coiling: a two-center retrospective study - Zhang, Xuexian; Wang, Ruidong; Ding, Yuhan; Li, Wei; Ren, Hong; Zhang, Jun (Frontiers in Neurology, 2023)
Background The management of middle cerebral artery (MCA) aneurysms remains a controversial topic, and MCA aneurysms have traditionally been treated primarily by surgical clipping. The Neuroform Atlas Stent™ (NAS, available from Stryker Neurovascular, Fremont, California) represents the latest generation of intracranial stents with improved stent delivery system capabilities. Objective This study aims to investigate the safety, feasibility and efficacy exhibited by NAS in treating unruptured aneurysms at the MCA bifurcation. Methods This was a two-center retrospective study involving 42 patients with unruptured wide-necked aneurysms (WNAs) of the MCA treated with the NAS from October 2020 to July 2022. Results The stent was used to treat 42 cases of unruptured WNA at the MCA bifurcation. Endovascular treatment techniques had a 100% success rate. Immediate postoperative angiography found complete aneurysm occlusion in 34 patients (80.9%) (mRRC 1), neck remnant in 7 patients (16.7%) (mRRC 2), and residual aneurysm in 1 patient (2.4%) (mRRC 3). The thromboembolic complication rate was 2.4% (1/42). The follow-up period was 8.7 months on average (3–16 months). The last angiographic follow-up results revealed complete aneurysm occlusion in 39 patients (92.9%) (mRRC 1), neck remnant in 3 (7.1%) patients (mRRC 2), no aneurysm recanalization or recurrence, and no cases of stent intimal hyperplasia. During the latest clinical follow-up, all patients had an mRS score of 0. Conclusion Our study demonstrates that the NAS can be applied to treat unruptured WNAs at the MCA bifurcation with favorable safety, feasibility, and efficacy.